2015
DOI: 10.1016/j.amc.2014.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Stability and convergence of a new finite volume method for a two-sided space-fractional diffusion equation

Abstract: a b s t r a c tIn this paper, we consider a two-sided space-fractional diffusion equation with variable coefficients on a finite domain. Firstly, based on the nodal basis functions, we present a new fractional finite volume method for the two-sided space-fractional diffusion equation and derive the implicit scheme and solve it in matrix form. Secondly, we prove the stability and convergence of the implicit fractional finite volume method and conclude that the method is unconditionally stable and convergent. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Previous studies showed that finite volume methods are anticipated to have a second-order convergence rate with respect to the mesh size on a uniform mesh [9,13,20,27,28] without using a Richardson extrapolation. This is in contrast to the Meerschaert-Tadjeran finite difference scheme, in which a Richardson extrapolation is required to recover a second-order accuracy [18].…”
Section: Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that finite volume methods are anticipated to have a second-order convergence rate with respect to the mesh size on a uniform mesh [9,13,20,27,28] without using a Richardson extrapolation. This is in contrast to the Meerschaert-Tadjeran finite difference scheme, in which a Richardson extrapolation is required to recover a second-order accuracy [18].…”
Section: Scenariomentioning
confidence: 99%
“…Extensive research has been conducted in the development of numerical methods for fractional differential equations [5,7,9,10,[12][13][14]18,[26][27][28]. Because of the nonlocal nature of fractional differential operators, numerical methods for space-fractional differential equations usually generate full stiffness matrices and were traditionally solved via Gaussian elimination.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [18] derived the exact solution for the accelerating flow of a generalized Oldroyd-B equation by utilizing the fractional calculus approach and discrete Laplace transform. Feng et al [19] studied the stability of a two-sided space-fractional diffusion equation. Liu et al have proposed some numerical methods for related fractional partial differential equations [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, numerical methods must be applied. At present, the major numerical methods are finite element methods(FEM) [2][3][4] [5], finite difference methods (FDM) [6] [7], finite volume methods(FVM) [8][9] [10]. However, when the FEM or FDM are used to solve the NCDE, it exhibits excessive numerical diffusion and nonphysical oscillation [11].…”
Section: Introductionmentioning
confidence: 99%